2014
DOI: 10.1002/jib.143
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of stuck wine fermentations using salt-preconditioned yeast

Abstract: The influence of salt (sodium chloride) on the cell physiology of wine yeast was investigated. Cellular viability and population growth of three wine-making yeast strains of Saccharomyces cerevisiae, and two non-Saccharomyces yeast strains associated with wine must microflora (Kluyveromyces thermotolerans and K. marxianus) were evaluated following salt pre-treatments. Yeast cells growing in glucose defined media exposed to different sodium chloride concentrations (4, 6 and 10% w/v) exhibited enhanced viabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
3
1
0
2
Order By: Relevance
“…Concerning all the fermented media with the same glucose concentration, they appeared to have almost the same cell number at the end of fermentation (Figure 1), thus indicating that NaCl stress for the same glucose concentration had almost no impact on the cell viability at the end of the fermentation ( Figure 1). As a general rule, the viability results were in accordance with the results reported by Logothetis et al (2014), which suggested that salt pre-culturing of yeast S. cerevisiae impacts positively on cell viability [36].…”
Section: Cell Viabilitysupporting
confidence: 81%
See 2 more Smart Citations
“…Concerning all the fermented media with the same glucose concentration, they appeared to have almost the same cell number at the end of fermentation (Figure 1), thus indicating that NaCl stress for the same glucose concentration had almost no impact on the cell viability at the end of the fermentation ( Figure 1). As a general rule, the viability results were in accordance with the results reported by Logothetis et al (2014), which suggested that salt pre-culturing of yeast S. cerevisiae impacts positively on cell viability [36].…”
Section: Cell Viabilitysupporting
confidence: 81%
“…These results cannot be compared with other researchers' results that used the same yeast strain with salt pre-culturing (NaCl 6% w/v) but in an even denser glucose medium (550 g/L), as cell viability values are not given [41]. Our results were in accordance with the observations of other researchers who found that NaCl pre-cultured yeast cells showed an increased cell viability at the end of the fermentation process [36]. Despite this increase, for all samples, after 192 h of fermentation, cell viability was lower compared to the values of the second peak.…”
Section: Cell Viabilitysupporting
confidence: 48%
See 1 more Smart Citation
“…Απηφ επαλαιακβαλφηαλ ηξεηο θνξέο. ηε ζπλέρεηα γηλφηαλ πξνζδηνξηζκφ ηνπ ζπλνιηθνχ αξηζκνχ ησλ θπηηάξσλ θαη ηεο βησζηκφηεηαο απηψλ ζην θάζε εκβφιην ψζηε ν ηειηθφο αξηζκφο ηνπ εκβνιίνπ λα είλαη 5x10 5 δσληαλά θχηηαξα αλά ml γηα ηνλ εκβνιηαζκφ 1000 ml ππνζηξψκαηνο [284]. Τν αηώξεκα ςύρζεθε ζηνπο 28 o C θαη θπγνθεληξήζεθε (5000 rpm/10 min) [262,263].…”
Section: πποεηοιμαζία εμβολίοςunclassified
“…(2010) NaCl νδεγεί ζε κείσζε ηνπ ζπλνιηθνύ αξηζκνύ ησλ θπηηάξσλ ελώ γηα ζπγθεληξώζεηο NaCl κεγαιύηεξεο από 5% w/v, ηα θύηηαξα ζην ηέινο ηεο δύκσζεο εκθαλίδνπλ κεγαιύηεξε βησζηκόηεηα. Σύκθσλα πάληα κε ηνπο ίδηνπο ζε άιιεο εξγαζίεο, ε ζπγθέληξσζε NaCl 6% w/v ήηαλ απηή πνπ έδσζε ηα θαιύηεξα απνηειέζκαηα ζε θπηηαξηθή βησζηκόηεηα θαη αλάπηπμε ζε ζρέζε κε άιιεο ζπγθεληξώζεηο NaCl ζε ζπλζεηηθά κέζα αλάπηπμεο[284,285]. Σηα ίδηα ζπκπεξάζκαηα ζρεηηθά κε ηε κείσζε ηνπ ζπλνιηθνύ αξηζκνύ ησλ θπηηάξσλ ππό ζπλζήθεο νζκσηηθνύ ζηξεο ηεο γιπθόδεο θαη ηεο παξαγόκελεο αηζαλόιεο αλαθέξνληαη θαη από ηνπο Pratt θαη ζπλ.…”
unclassified